Micro Credit and Poverty Alleviation in Nigeria: Evidence from Selected Agribusiness Cooperative Societies in Oyo State - Ibrahim, Majeed Ajibola; Gbadebo, Adedeji Daniel; Dada, Olawale Bamidele (Yayasan Ilomata, 2024)
Poverty is one of the world's biggest issues, particularly in third-world countries. Nigeria is not an exception to the rule that governments everywhere have been developing various economic and social policies or programs to lower the poverty rate inside their borders. It is well known that cooperative groups, particularly at the medium and micro levels, have proven essential to economic progress. This study investigates the impact of micro-credit on poverty eradication in Nigeria. To examine whether microcredit facilitates a decline in poverty, we use a simple linear model to test the hypothesis that cooperative societies greatly impact poverty, using primarily sourced data from Cooperative Societies in Oyo State. The impact of timely access to micro-credit, credit lending rate, and technical support have negative and significant coefficients of -0.229, -0.242, and -0.231. This supposes that any increase in all variables will result in a drop in poverty alleviation among agribusiness cooperators. The outcome demonstrates that a cooperative society has significantly raised the living standards of its members. This shows that cooperative societies are important in reducing poverty. They offer financial and technical services, which help low-income earners whom traditional financial institutions do not primarily support. We suggest using legislative approaches to keep cooperative societies relevant to Nigeria's efforts to reduce poverty.